Characterization of the Tyrosinase Gene of Aquarium-Maintained Nyalian Fish (Rasbora sp.) - Suryani, Sang Ayu Made Putri; Sadguna, Dewa Nyoman; A, AA Putri Risa; Pratama, Agus Surya; Rejeki, Dewi Seri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Rasbora fish is a local Indonesian fish whose population has decreased. In the Province of Bali this fish is called the Nyalian fish and no one has cultivated this fish. Nyalian fish in Bali Province are used as consumption fish and have potential as freshwater ornamental fish. Catching Nyalian fish continuously can cause this fish decrease in population and can cause extinction. Nyalian fish conservation can be done by domestication and adapting fish caught from their natural habitat to aquaculture aquarium, then used in aquaculture activities and ensuring continuity of numbers and avoiding extinction. During the domestication process, the Nyalian fish will experience stress due to changes in their habitat. Stress in fish can be shown by a drastically darker body condition. Parts of the body that blacken or show a darker color are due to the activity of melanin as an active role in it. The Tyrosinase gene is one of the genes responsible for coding pigment patterns. The TYR gene has an important role in instructing the formation of the enzyme Tyrosinase.